2010
DOI: 10.1158/1541-7786.mcr-09-0296
|View full text |Cite
|
Sign up to set email alerts
|

CNK1 Promotes Invasion of Cancer Cells through NF-κB–Dependent Signaling

Abstract: Hallmarks of cancer cells are uncontrolled proliferation, evasion of apoptosis, angiogenesis, cell invasion, and metastasis, which are driven by oncogenic activation of signaling pathways. Herein, we identify the scaffold protein CNK1 as a mediator of oncogenic signaling that promotes invasion in human breast cancer and cervical cancer cells. Downregulation of CNK1 diminishes the invasiveness of cancer cells and correlates with reduced expression of matrix metalloproteinase 9 (MMP-9) and membrane-type 1 MMP (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…Recent studies have shown that downregulation of CNK (Connector enhancer of KSR) proteins which are scaffold proteins regulating mitogen-activated protein kinase pathways, diminishes the proliferation and invasiveness of cancer cells, particularly breast cancer cells [21,35]. Remarkably, we also observed that Smurf2 knockdown caused a considerable downregulation in the expression of CNKSR2, a CNK homolog, followed by a concomitant decrease in the proliferation of breast cancer cells (Figures  7 and 8).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Recent studies have shown that downregulation of CNK (Connector enhancer of KSR) proteins which are scaffold proteins regulating mitogen-activated protein kinase pathways, diminishes the proliferation and invasiveness of cancer cells, particularly breast cancer cells [21,35]. Remarkably, we also observed that Smurf2 knockdown caused a considerable downregulation in the expression of CNKSR2, a CNK homolog, followed by a concomitant decrease in the proliferation of breast cancer cells (Figures  7 and 8).…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, knockdown of hCNK2 in PC12 prevented NGF-dependent ERK activation as well as neurite outgrowth. It thus appears that CNK proteins can mediate RTK-specific signals and that their function is not restricted to RAS/ERK signaling [35]. In our study we observed that downregulation of CNKSR2 expression following Smurf2 knockdown did not affect the MEK, ERK and NF-kB signaling cascades.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Assays with secreted embryonic alkaline phosphatase (SEAP) as reporter under the control of the serum response factor (SRF) activated by ERK signalling were performed to monitor the RAF-MEK-ERK pathway20. Matrix metalloproteinase 14 (MMP14) promoter-controlled luciferase reporter assays were used to measure AKT signalling8. Inhibitor treatment confirmed that SRF reporter activation depends on ERK signalling and MMP14 promoter activation on AKT signalling (Supplementary Figure S1A,B).…”
Section: Resultsmentioning
confidence: 91%
“…CNK1 drives AKT-dependent cell proliferation and co-localizes with AKT at the plasma membrane in invasive breast cancer tumours7. In addition, CNK1 promotes invasion of cancer cells by AKT-dependent NFκB pathway activation8. Insulin recruits CNK1 complexed with ARF guanine nucleotide exchange factors of the cytohesin family to the plasma membrane facilitating PI3K/AKT signalling9.…”
mentioning
confidence: 99%